2012
DOI: 10.4172/2161-1025.1000110
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Prognostic Significance of R282W p53 Gene Mutation in North India Patients with Non Small Cell Lung Cancer

Abstract: Background: p53 plays a central role in protecting the integrity of the genome. Its activity is ubiquitously lost in cancers, either by inactivation of its protein (p53 pathway) or by mutation in the p53 gene, thereby indicating its importance in understanding cancer and as a therapeutic target. Given the high frequency of the hotspot R282W p53 gene mutation in our NSCLC patients, we have evaluated the association of R282W mutation with the progression of the malignancy.Methods: Blood DNA was extracted from ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…Analysis of patient 2’ FFPE STS tissue revealed the same mutation at high frequency (79%), providing strong evidence for the tumoural shedding of DNA into the circulation in this case. This is further supported by TP53 _p.R282W's previously association with multiple mesenchymal tumours [ 23 , 24 ], as well as early and late stage lung cancer patients where an association with progressive disease has been identified [ 25 ].…”
Section: Discussionsupporting
confidence: 57%
“…Analysis of patient 2’ FFPE STS tissue revealed the same mutation at high frequency (79%), providing strong evidence for the tumoural shedding of DNA into the circulation in this case. This is further supported by TP53 _p.R282W's previously association with multiple mesenchymal tumours [ 23 , 24 ], as well as early and late stage lung cancer patients where an association with progressive disease has been identified [ 25 ].…”
Section: Discussionsupporting
confidence: 57%
“…Rashid and colleagues found a significantly higher frequency of R282W P53 mutation (58%) between Chronic myeloid leukemia patients in the Indian population (23). Javid and colleagues found that 62% of patients with Nonsmall cell lung cancer were positive for R282W P53 mutation in India (35). Besides, point mutations at codon 282 are mutational hotspots reported in hematologic diseases, including Burkitt's lymphoma (36), Myelodysplastic syndrome (37), T-cell leukemia (38), Lymphoid leukemia (39) and etc.…”
Section: Discussionmentioning
confidence: 99%